Rapid Quantification of NETs In Vitro and in Whole Blood Samples by Imaging Flow Cytometry. Issue 5 (15th April 2019) - Lelliott, Patrick M.; Momota, Masatoshi; Lee, Michelle S.J.; Kuroda, Etsushi; Iijima, Norifumi; Ishii, Ken J.; Coban, Cevayir
Abstract: Neutrophil extracellular trap (NET) formation involves the release of DNA outside the cell to neutralize pathogens. Techniques such as live microscopy, flow cytometry, and intravital imaging allow the characterization of NETs, but these either cannot be applied in vivo, lack specificity or require invasive procedures. We developed an automated analysis method to rapidly acquire and characterize cells as NETs or NET precursors, as opposed to cells undergoing other forms of cell death, using imaging flow cytometry. NETs were maintained in solution using a novel three‐dimensional cell culture system in which cells are suspended at the interface of two liquids of different density. Critically, we identify NETs using an image analysis algorithm based on morphological data showing the extrusion of DNA beyond the cell boundaries. In vitro, we used this technique to demonstrate different requirements for NET formation in human and mouse neutrophils. We also measured NETs in whole blood during infection of mice with the malaria parasite Plasmodium yoelii . We expect this technique will provide a valuable approach to better understand the process of NET formation and its importance in disease. © 2019 International Society for Advancement of Cytometry Abstract :